Exploring classroom management in the teaching of English - Asma, Asma; Khairuni, Putri; Ayouni, Nour (Accentia: Journal of English Language and Education, 2025)
The goal of classroom management is to offer students supplementary learning opportunities. A teacher employs many tactics to efficiently organize students, such as allocating space, time, and resources, to enhance their learning process. The objective of this study is to examine the administration of classrooms at SMPN 1 Sukamakmur, Aceh Province, with a particular focus on the difficulties that instructors have as a result of insufficient resources. The study also seeks to examine the class management process that is associated with the instruction and acquisition of the English language. This study used a qualitative research design with descriptive approach. The study observed one English instructor who instructed a group of seventh-grade students as a representative sample, utilizing a combination of observation and interview as data gathering techniques. The results of the study illustrate the successful execution of classroom management, devoid of any facility-related problems. Moreover, the classroom management methods are in accordance with the lesson plan specified in the report.